Epilepsy Milestones 2.0: An updated framework for assessing epilepsy fellowships and fellows. Issue 8 (26th May 2022) - Thio, Liu Lin; Edgar, Laura; Ali, Imran; Farooque, Pue; Holland, Katherine D.; Mizrahi, Eli M.; Shahid, Asim M.; Shin, Hae Won; Yoo, Ji Yeoun; Carlson, Chad
Abstract: Objective: Accreditation Council for Graduate Medical Education (ACGME)‐accredited epilepsy fellowships, like other ACGME accredited training programs, use Milestones to establish learning objectives and to evaluate how well trainees are achieving these goals. The ACGME began developing the second iteration of the Milestones 6 years ago, and these are now being adapted to all specialties. Here, we describe the process by which Epilepsy Milestones 2.0 were developed and summarize them. Methods: A work group of nine board‐certified, adult and pediatric epileptologists reviewed Epilepsy Milestones 1.0 and revised them using a modified Delphi approach. Results: The new Milestones share structural changes with all other specialties, including a clearer stepwise progression in professional development and the harmonized Milestones that address competencies common to all medical fields. Much of the epilepsy‐specific content remains the same, although a major addition is a set of Milestones focused on reading and interpreting electroencephalograms (EEGs), which the old Milestones lacked. Epilepsy Milestones 2.0 includes a Supplemental Guide to help program directors implement the new Milestones. Together, Epilepsy Milestones 2.0 and the Supplemental Guide recognize advances in epilepsy, including stereo‐EEG, neurostimulation, genetics, and safety in epilepsy monitoring units. Significance: Epilepsy Milestones 2.0 address the shortcomings of the old Milestones and should facilitate the assessment of epilepsy fellowships and fellows by program directors, faculty, and fellows themselves.